Literature Review of Occupational Health and Safety in Oil Palm Plantations - Aisyahfira Anindya; Daru Lestantyo; Yuliani Setyaningsih (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: The palm oil industry presents high occupational accident risks due to heat exposure, heavy machinery, noise, chemicals, and low compliance with personal protective equipment (PPE). Therefore, Occupational Health and Safety (OHS) implementation is essential to protect workers and support productivity. Objective: This study aims to determine the overview of OHS implementation in palm oil plantations and palm oil processing factories based on previous research findings. Method: This study used a literature review method. Article searches were conducted through Google Scholar, PubMed, and Science Direct databases during the period 2021–2026 using keywords related to OHS implementation in the palm oil industry. From 200 identified articles, 12 articles met the inclusion criteria and were analyzed. Results and Discussion: OHS implementation reduced accident risks and improved productivity. Risk identification methods, including HAZOP, Job Safety Analysis (JSA), and HIRARC, helped identify hazards and determine controls. However, implementation barriers included low worker awareness, poor PPE compliance, limited training, weak supervision, traditional work culture, and low education. Conclusion: The implementation of OHS in the palm oil industry is very important in creating a safe, healthy, and productive work environment. Improving training, supervision, and workers’ awareness regarding the importance of OHS should be carried out continuously